RELATION BETWEEN THE ENERGY OF EARTHQUAKE SWARM AND THE HURST EXPONENT OF RANDOM VARIATIONS OF THE GEOMAGNETIC FIELD - Hayakawa M.; Hattori K.; Nickolaenko A.P.; Rabinowicz L.M. (My University, 2004)
We present evidence that the Hurst exponent of the ultra low frequency component of the geomagnetic field varies similarly to the energy release of the local swarm of earthquakes observed in Japan in 2000. Similarity is demonstrated between the energy release by the shocks and variations of the Hurst exponent derived for the three component records of the geomagnetic field.